Integration of Frequency Domain Wideband Antenna Nulling and Wavenumber Domain Image Formation for Multi-Channel SAR - M. Bucciarelli; D. Pastina; D. Cristallini; M. Sedehi; P. Lombardo (International Journal of Antennas and Propagation)
A Multichannel Synthetic Aperture Radar (M-SAR) exploiting an antenna nulling based Electronic Counter-Counter Measures (ECCM) technique shall be able to cancel the effects of noise-like interferences over the collected SAR data. Since SAR systems often work with wide bandwidths to provide high resolution images, ECCM technique must account for the presence of wideband interference signal. In this paper we consider a wideband antenna nulling technique based on space-frequency adaptive nulling and we propose an integration of the WB antenna nulling scheme within the focusing algorithm for M-SAR systems, thus allowing a fusion between ECCM and usual SAR processing steps. The computational cost of the integrated algorithm is compared with the cost of more traditional sequence of the wideband extension of the Side-Lobe Canceller and the focusing operation, to show the computational feasibility of the proposed integrated algorithm. The possibility to perform suboptimally the space-frequency adaptive nulling is also considered.